Pelatihan Digitalisasi Rekam Medis Dalam Persiapan Implementasi RME Di RSGM Maranatha - Leni Herfiyanti (Universitas Mercu Buana, 2023)
Routine and quality data integration is a component that must be realized in digital transformation. In health care facilities, this digital transformation is urgently needed for continuity of patient medical history information and to facilities the process of managing complex health data. One of the digital transformations needed is in the field of medical records and health information. Digitization of medical records is the process of converting medical records document media into a digital document. RSGM Maranatha has implemented hospital information system but not yet based on Electronic Medical Records (EMR), several applications have not been integrated and medical records still manual. Digitization of medical records is expected to supports the preparation for the implementation of EMR at RSGM Maranatha. The solution to solving these problems is by holding training activities. Training activities are carried out by counseling, demonstrations starting from how to scan, save and import files as well as a reflection process to assess the success of the activity. The pre and post tests show an increase in knowledge and understanding regarding the digitization of medical records. The application of digitizing medical records at RSGM Maranatha can already by applied.